2018
DOI: 10.3233/jad-180738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ocular Perfusion in Alzheimer’s Disease Using Optical Coherence Tomography Angiography

Abstract: Background: There is increasing evidence for the involvement of cerebrovascular factors in Alzheimer's disease (AD). Objective: To evaluate retinal and optic nerve head perfusion in patients with AD using optical coherence tomography angiography (OCTA), and to analyze the correlations of quantitative OCTA metrics with AD pathology and vascular cerebral lesions in AD patients. Methods: 36 eyes of 36 patients with AD (study group) and 38 eyes of 38 healthy subjects (control group) were prospectively included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 39 publications
8
110
0
3
Order By: Relevance
“…We showed that AD participants have a sparser VD of the SCP compared with control participants. Our ndings support most of the previous OCTA studies in AD participants (Table 4), [12][13][14]16] which is in keeping with studies on larger retinal vessels using fundus photographs. [3,33] It should be noted that two other studies did not observe any differences in the VD of the SCP in AD participants.…”
Section: Scp In Ad Individualssupporting
confidence: 91%
See 3 more Smart Citations
“…We showed that AD participants have a sparser VD of the SCP compared with control participants. Our ndings support most of the previous OCTA studies in AD participants (Table 4), [12][13][14]16] which is in keeping with studies on larger retinal vessels using fundus photographs. [3,33] It should be noted that two other studies did not observe any differences in the VD of the SCP in AD participants.…”
Section: Scp In Ad Individualssupporting
confidence: 91%
“…[10] While there are a few OCTA studies investigating AD, there have been mixed conclusions. [11][12][13][14][15] Some researchers reported nding signi cant reduction in the vessel density (VD) only in the super cial plexus, [14,16] which complements histology ndings [10] and OCT studies [9] since the super cial plexus mainly supplies the inner retinal layer. [17] However, others reported nding changes only in the deep plexus.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…They found a reduction in the density of vessels in SVP in the eyes of AD compared to HC [18]. Subsequent research groups con rmed a decrease in retinal vascular density in SVP in patients diagnosed with AD [46][47][48]. Jiang et al found a slight decrease in GC-IPL thickness in AD compared with MCI and HC.…”
Section: Discussionmentioning
confidence: 97%